The blockchain, plums, and lemons: Information asymmetries & transparency in decentralized markets - Benedikt Notheisen; Christof Weinhardt (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2019)
Despite a growing interest, researchers and practitioners still struggle to transfer the blockchain concept introduced by Bitcoin to market-oriented application scenarios. To shed light on the technology's usage in markets with asymmetric information, this study analyzes the effect of the blockchain's public transparency paradigm on behavioral patterns and market outcomes. In line with prior research, our findings indicate that the blockchain's shared record mitigates adverse selection effects and reduces moral hazard of good market participants (plums). In addition, we identify an incentive for bad market participants (lemons) to behave opportunistically in the presence of perfect quality information. More specifically, the disclosed information allows them to learn about quality differences between plums and lemons, deceive their counterparties, and move to a new equilibrium with increased utility. As a result, the market collapses despite a welfare gain and future generations are denied market access. In addition, plums and lemons are committed to inefficient equilibria following irrational behavior. In total, this study aims to provide initial guidance for blockchain adoption in the context of markets with information asymmetries and highlights risks that arise from competition, the exposure to irrational behavior, and the implementation of services on the infrastructure level.
urn:nbn:de:swb:90-924863
Keywords: D53; D82; G21; L86; 330; Blockchain; Transparency; Market for Lemons; FinTech; Moral Hazard; Information Sharing; Credit Markets